PRT simulation in an immersive virtual world - Cristina V. Lopes (2008)
Immersive virtual world environments, such as Second LifeTM (SL), have the potential to dramatically improve the process of analyzing usability within technically correct system simulations, long before the system is built. We report our findings with the SL simulation of a Personal Rapid Transit (PRT) system. The SL model and simulation were done according to the original technical specifications. In interacting with this simulation, the system designers were able to identify several usability issues that would have gone unnoticed in a non-immersive simulation environment. Namely: (1) a problem with the design of the offramp to the station; (2) further requirements for the design of the top of the vehicles, so that the suspended track is out of direct sight of the people inside; (3) further safety requirements for dealing with unexpected obstacles along the path. While all of these issues would have been identified upon deployment of the physical prototype, the contribution of our work is to show how usability issues like these can now be identified much earlier, using simulations in a virtual world. Copyright Â© 2008 ICST.